1993
DOI: 10.1021/bi00088a040
|View full text |Cite
|
Sign up to set email alerts
|

Autocatalytic generation of Dopa in the engineered protein R2 F208Y from Escherichia coli ribonucleotide reductase and crystal structure of the Dopa-208 protein

Abstract: The mutant form Phe-208-->Tyr of the R2 protein of Escherichia coli ribonucleotide reductase contains an intrinsic ferric-Dopa cofactor with characteristic absorption bands at 460 and ca. 700 nm [Ormö, M., de Maré, F., Regnström, K., Aberg, A., Sahlin, M., Ling, J., Loehr, T. M., Sanders-Loehr, J., & Sjöberg, B. M. (1992) J. Biol. Chem. 267, 8711-8714]. The three-dimensional structure of the mutant protein, solved to 2.5-A resolution, shows that the Dopa is localized to residue 208 and that it is a bidentate l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
52
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 24 publications
4
52
0
Order By: Relevance
“…When R2-Y122H was isolated from cells grown in iron-free minimal medium, we obtained a similar optical spectrum without the bands at 325 and 370 nm (not shown). In consistency with previous studies of wild-type R2 from iron-free growth medium (27); however, a residual amount of up to 0.2 irons/ dimer could also be detected here using the bathophenanthroline assay.…”
Section: Expression Of R2-y122h-supporting
confidence: 93%
See 2 more Smart Citations
“…When R2-Y122H was isolated from cells grown in iron-free minimal medium, we obtained a similar optical spectrum without the bands at 325 and 370 nm (not shown). In consistency with previous studies of wild-type R2 from iron-free growth medium (27); however, a residual amount of up to 0.2 irons/ dimer could also be detected here using the bathophenanthroline assay.…”
Section: Expression Of R2-y122h-supporting
confidence: 93%
“…Expression and Purification-The cells carrying the R2-Y122H mutation were grown either in Luria-Bertani (LB) medium, or in minimal medium (27). Both media contained carbenicillin 50 mg/ml and kanamycin 50 mg/ml.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that apo-PMI is extemely unstable and in the absence of a stabilising metal or chaotropic solution will precipitate. This prevented direct investigation of possible autocatalytic hydroxy!ation of tyrosine as seen in R2 F208Y ribonucleotide reductase (Aberg et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The Dopa thus formed chelates high-spin Fe(II1) giving rise to characteristic ligand to metal charge transfer bands at 460 nm and 700 nm. This reaction proceeds both in vivo (Ormo et al, 01992) and in vitro utilising purified apoprotein and iron salts (Aberg et al, 1993).…”
Section: Discussionmentioning
confidence: 99%